Search for new particles in events with one lepton and missing transverse momentum in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, G. (2014)
This paper presents a search for new particles in events with one lepton (electron or muon) and missing transverse momentum using 20.3 fb−1 of proton-proton collision data at s√=8 TeV recorded by the ATLAS experiment at the Large Hadron Collider. No significant excess beyond Standard Model expectations is observed. A W′ with Sequential Standard Model couplings is excluded at the 95% confidence level for masses up to 3.24 TeV. Excited chiral bosons (W∗) with equivalent coupling strengths are excluded for masses up to 3.21 TeV. In the framework of an effective field theory limits are also set on the dark matter-nucleon scattering cross-section as well as the mass scale M∗ of the unknown mediating interaction for dark matter pair production in association with a leptonically decaying W.